Doctoral Creative Music: The Contemporary Vocal Literature of Siamese Art Songs for Piano and Voice - Tainchaivanich, Poonsant; Premananda, Weerachat; Israngkun, Tongsuang (Parichart Journal, 2024)
“Doctoral Creative Music: The Contemporary Vocal Literature of Siamese Art Songs for Piano and Voice,” aimed to create the literature for piano and voice which represents Thai Traditional music in a modern aspect as well as to combine western music and traditional Thai music together. In the research process, existing literature has been reviewed, including music literature for piano and voice, the role of piano accompaniment in vocal music, traditional Thai piano repertoire crafted by the masters, and Traditional Thai piano music in the 21st century. The research has developed a unique method in applying western music theory and compositional techniques to Traditional Thai melodies in western composing process. After several practicing sessions along with polishing the works based on the ideas of western music interpretation and theory, six pieces of music for piano and voice have been finally produced.